A senses-based model for experiential tourism - Meacci,Luca (2018)
An experience can be defined as the triggered stimulation of the senses, the heart, and the mind. Senses play a central role in our perception of the surrounding world. Therefore, the study of the sensory dimension of tourist experiences is pivotal to visitor management in the tourism industry. In particular, recent studies showed that a successful tourism destination should attract tourists through a systematic approach based on stimuli for all the senses. In this article, we refer to the case of a multisensory criteria model applied in a tourism destination in Fiesole, Italy, a town located on one of the hills surrounding Florence. Our aim is to provide a critical illustration of the various steps and outcomes of a tourism experience design. Findings show that not only the gathering of tourism-senses experiential concepts, but also the logical order expressed by the experience process is critical. Therefore, we have provided a theoretical framework for the foundation of a sensory-based model, which in addition to being an innovative subject of tourism research can result in an easy-to-use tool for operators to plan, monitor and evaluate tourist experiences.